1992
DOI: 10.1177/000456329202900206
|View full text |Cite
|
Sign up to set email alerts
|

Serum Urate, Serum Glucose and Diabetes

Abstract: SUMMARY. We have studied the relationship between serum glucose and urate in 260 699 men and 214 118 women from Sweden, and 140084 men and 30653 women from the UK. We found an increase in mean serum urate with increasing glucose concentrations up to 7'OmmollL in men and 9'OmmollL in women. Thereafter increasing glucose values were accompanied by a statistically significant decrease in urate concentrations. This fall was particularly marked in younger subjects. We believe this may have important implications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 8 publications
6
31
1
Order By: Relevance
“…Corresponding ORs for hyperuricaemia as an outcome showed 0.24 (95% CI 0.09 to 0.67) among men and 0.51 (95% CI 0.25 to 1.03) among women 5. Similarly, studies have shown that a history of diabetes was significantly associated with lower levels of serum uric acid48 and the inverse association was significantly stronger among men than women 5. These previous data based on serum uric acid, the causal intermediate of gout, closely agree with the current study findings based on gout, the clinical outcome.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Corresponding ORs for hyperuricaemia as an outcome showed 0.24 (95% CI 0.09 to 0.67) among men and 0.51 (95% CI 0.25 to 1.03) among women 5. Similarly, studies have shown that a history of diabetes was significantly associated with lower levels of serum uric acid48 and the inverse association was significantly stronger among men than women 5. These previous data based on serum uric acid, the causal intermediate of gout, closely agree with the current study findings based on gout, the clinical outcome.…”
Section: Discussionmentioning
confidence: 95%
“…For example, several previous studies have shown that individuals with type 2 diabetes (or blood glucose >10 mmol/litre (180 mg/dl)) have substantially lower serum uric acid levels than normal individuals, likely due to the uricosuric effect of glycosuria 48. Furthermore, the impaired inflammatory response observed in diabetes may play a protective role against the risk of gout, which is the direct result of an intense inflammatory response to urate crystals 9.…”
Section: Introductionmentioning
confidence: 99%
“…Serum uric acid increases with glucose concentrations up to 120-145 mg/dl [28,29]. Thereafter, glucose values have been negatively correlated with uric acid levels most likely due to an enhanced renal excretion rate of uric acid, possibly by reduced reabsorption in the proximal tubuli.…”
Section: Discussionmentioning
confidence: 99%
“…Modest elevations in blood glucose levels in diabetic patients were associated with hyperuricemia (Whitehead et al, 1992). It is important to note that glucose significantly increased human urate transporter/channel (hUAT) open probability, suggesting a role for extracellular glucose in regulating hUAT channel activity (Whitehead et al, 1992;Gonzalez-Sicilia et al, 1997;Leal-Pinto et al, 2002). The transport abnormalities were reversed by correction of blood sugar levels (Gonzalez-Sicilia et al, 1997).…”
Section: Discussionmentioning
confidence: 99%